The Effectiveness of Quizizz as a Media to Facilitate English Reading Learning at an Indonesian Islamic Junior Secondary School - Putri Ayu Lestari; Misnariah Idrus; Hasbullah Hasbullah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to examined whether the use of Quizizz could improve the English reading achievement of eighth-grade students at MTs Emeyodere Sorong. The study employed a pre-experimental method using a one-group pre-test and post-test design. The participants were 12 students selected through total sampling. Data were collected through reading comprehension test administered before and after the implementation of Quizizz and were analyzed using descriptive and inferential statistics. The result showed that students’ reading achievement improved after the treatment. The mean score increased from 34.75 on the pre-test to 51.75 on the post-test indicating a gain of 17 points. The paired-samples t-test showed a statistically significant difference between the pre-test and post-test scores (t = -4.092, p .001), indicating that students performed significantly better after the treatment. In addition, the regression analysis demonstrated a significant effect of Quizizz on students’ reading achievement (F= 12.256, p = .006). These findings are consistent with previous studies that reported the positive impact of Quizizz on students’ engagement, motivation, and reading performance. Therefore, Quizizz can be considered an effective learning medium for enhancing students’ reading achievement.